The Doctors' 5-Minute Health Fixes : The Prescription for a Lifetime of Great Health - Aalst, Mariska van (Emmaus Rodale Inc, 2010)
The hosts of the popular health show "The Doctors" offer five-minute fixes, culled from the latest medical journals, that will lead to the most vibrant, happiest, longest lives.
Include Color Illustration and Index
Keywords: Health -- Self-care, Health